Hypertensive Heart Failure with Severe Arteriosclerotic Stenosis of the Descending Aorta - 김정아; 김동빈; 장성원; 권범준; 조은주; 송준호; 임창훈; 노태호; 김재형; 박찬범; 송경섭 (Korean circulation journal, 2007)
We report a case of hypertensive heart failure with severe stenosis of the descending aorta. The patient had hyper-tension;therapy for 2 weks, he was admited to our hospital for acute heart failure. Computed tomography (CT) and mag-netic resonance imaging (MRI) showed severe arteriosclerotic stenosis of the descending aorta above the renal artery bifurcation. He underwent aortic resection and grafting. After surgery, his condition improved, and he was dis-charged. KCI Citation Count: 1